CGIAR Guidelines for Ethical Engagement with Gender-based Violence in Food Systems Research - CGIAR GENDER Impact Platform (CGIAR GENDER Impact Platform, 2024)
Gender-based violence (GBV) is widespread across agrifood systems, but often overlooked in the context of food systems research (Forsythe 2023). CGIAR research, and food systems research more generally, may not be directly focused on addressing issues of GBV, or even gender issues per se, but the issue of GBV may also arise in other research situations, and researchers must be prepared to respond to such instances appropriately and ethically. Moreover, precautions must be taken to ensure that any research involving human subjects or impacting humans does not cause harm, including by unintentionally increasing the incidence of GBV. The potential impacts of both the research process on participants and the potential longer-term, reverberating effects of interventions, including introduced technologies, need to be considered carefully during the design, implementation, and evaluation phases. These guidelines aim to support researchers working on agrifood systems to more carefully, competently, and ethically enga